BATAM'S REPUTATION AS A TOURISM CITY IN THE DIGITAL ERA - Purwanti, Angel (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2026)
Tourism reputation has become a critical intangible asset in the digital era, influencing tourists’ perceptions, trust, and destination competitiveness. This study aims to examine Batam City’s reputation as a tourism destination based on tourists’ perceptions, focusing on four key dimensions: credibility, reliability, trustworthiness, and social responsibility. A quantitative explanatory approach was employed using a survey method. Data were collected from 347 tourists who had visited Batam City and accessed digital tourism information, including social media and online reviews. The data were analyzed using descriptive statistics and reliability testing in PSPP. The results indicate that all reputation dimensions are perceived positively by tourists, with credibility showing the highest mean score, followed by social responsibility, trustworthiness, and reliability. Reliability testing demonstrates that all measurement dimensions have acceptable to excellent internal consistency. These findings suggest that Batam’s tourism reputation is shaped not only by service performance but also by institutional trust and socially responsible tourism practices in the digital environment. The study provides empirical insights for destination managers and policymakers to strengthen Batam’s reputation through consistent service quality and strategic digital communication.